Hexafluoroisopropyl N-Fluorosulfonyl Carbamate: Synthesis and Its Facile Transformation to Sulfamoyl Ureas - Liu, Shuo; Li, Xixi; Wang, Xiaolei; Xu, Long; Dong, Jiajia (Synthesis, 2024)
The synthesis of hexafluoroisopropyl N-fluorosulfonyl carbamate (HFC) and its facile transformation to sulfamoyl ureas are reported . Unlike liquid chlorosulfonyl isocyanate (CSI) and fluorosulfonyl isocyanate (FSI), which are corrosive and moisture-sensitive, HFC is a white solid and displays satisfactory bench-stability and unique reactivity, which facilitates its double ligation with amines to directly afford a series of sulfamoyl ureas under ambient conditions. It is worth noting that HFC will serve as an efficient surrogate to CSI and FSI for laboratory use, especially for accessing the bioactive sulfamoyl ureas under mild conditions.
Keywords: sulfamoyl ureas; reagent; hexafluoroisopropanol; bench-stability; DABCO